2017
DOI: 10.3233/nre-171478
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of a combined therapeutic approach in the management of Pisa Syndrome

Abstract: These data highlight the need for accurate characterization of PS focusing on the role of abdominal muscles and the need for a specific rehabilitation protocol for PS management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 15 publications
0
15
0
Order By: Relevance
“…In favor of dystonic etiology, several EMG investigations have reported tonic activation of paraspinal or abdominal muscles ipsilateral to the leaning side in PD patients with PS 4 6 , 20 , 34 . However, this pattern was not observed in our PD-PS.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In favor of dystonic etiology, several EMG investigations have reported tonic activation of paraspinal or abdominal muscles ipsilateral to the leaning side in PD patients with PS 4 6 , 20 , 34 . However, this pattern was not observed in our PD-PS.…”
Section: Discussionmentioning
confidence: 99%
“…These contradictory findings might reflect methodological variability, including muscles explored and EMG recording paradigm, or different patient characteristics, such as disease severity and duration of PS. Indeed, we did not specifically examine EMG activity of the abdominal muscles, such as the external oblique, which are a potential target of lidocaine injection therapy to ameliorate PS 34 . Nevertheless, there have been arguments against dystonic hypothesis, due to a paucity of clinical features compatible with dystonia in PS, including overflow, twisting or twitching, and aggravation with motion 1 , 2 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Only six studies were specifically designed to test the efficacy of non-invasive therapies (neurorehabilitation, botulinum toxin, or lidocaine injections) in patients with PS and PD ( 2 , 7 , 8 , 40 42 ), and among these only two were randomized controlled trials ( 2 , 40 ). Three studies used a kinematic analysis of movement for recording the outcome measures ( 2 , 7 , 41 ), but only two of them evaluated trunk ROM during dynamic tasks ( 2 , 7 ). The improvement achieved in our t-DCS group is consistent with previous data reporting a reduction between 30 and 50% of lateral trunk inclination and a comparable increase of ROM of trunk bending at the end of a rehabilitation program ( 2 , 7 , 8 , 40 42 ).…”
Section: Discussionmentioning
confidence: 99%
“…The main study limitations were pitfalls in study design, small sample size, different diagnostic criteria to define axial postural abnormalities, and use of one or more different measurement methods: standard goniometric measurement with a wall goniometer, smartphone, protractor, inclinometer or photographs was used in 22 studies, 40,47,48,50,51,57,58,[60][61][62][63][64][65][66]72,73,77,78,81,82,98,101 software-based measurement with NeuroPostureApp, Kinovea, MB Ruler ® software, or Image J was used in 12, [37][38][39]41,[44][45][46]49,51,52,56,97,99 Cobb angle, X-ray in nine, 42,43,55,71,79,81,[83][84][85] a spinal mouse electronic measuring device in one study 91 ; 26 studies reported no instrument, tool or bony reference points for evaluating axial postural abnormalities. 53,...…”
Section: Pathophysiology: Main Findingsmentioning
confidence: 99%